Identification of differentially expressed non-coding RNAs in the plasma of women with preterm birth - Waqasuddin Khan; Samiah Kanwar; Mohammad Mohsin Mannan; Furqan Kabir; Naveed Iqbal; Mehdia Nadeem Rajab Ali; Syeda Rehana Zia; Sharmeen Mian; Fatima Aziz; Sahrish Muneer; Adil Kalam; Akram Hussain; et al. (RNA Biology)
This study aimed to identify differentially expressed non-coding RNAs (ncRNAs) associated with preterm birth (PTB) and determine biological pathways being influenced in the context of PTB. We processed cell-free RNA sequencing data and identified seventeen differentially expressed (DE) ncRNAs that could be involved in the onset of PTB. Per the validation via customized RT-qPCR, the recorded variations in expressions of eleven ncRNAs were concordant with the in-silico analyses. The results of this study provide insights into the role of DE ncRNAs and their impact on pregnancy-related biological pathways that could lead to PTB. Further studies are required to elucidate the precise mechanisms by which these DE ncRNAs contribute to adverse pregnancy outcomes (APOs) and their potential as diagnostic biomarkers.